THE ROLE OF ARTIFICIAL INTELLIGENCE (AI) CHATBOTS IN DEVELOPING STUDENTS’ ENGLISH SPEAKING FLUENCY - Bekchanova Mahliyokhon Hamidjon kizi, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Artificial Intelligence (AI) has become one of the most influential technological innovations in modern education. The rapid development of digital technologies has changed traditional teaching methods and created new opportunities for interactive and personalized learning. In recent years, AI chatbots have gained significant popularity in  language  education  because  they  help  students  improve  communication  skills through continuous practice and real-time interaction. In English language learning, speaking fluency is considered one of the most important skills, as it allows learners to communicate  effectively  in  academic,  professional,  and  social  environments. However, many students experience difficulties in speaking English fluently because of limited vocabulary, pronunciation problems, fear of making mistakes, and lack of confidence.  Traditional  classroom  methods  often  cannot  provide  enough  speaking opportunities  for  every  learner  due  to  limited  lesson  time  and  large  class  sizes. Therefore,  the  integration  of  AI  chatbots  into  language  education  has  become  an effective solution for improving students’ oral communication skills.